Pengaruh Budaya Organisasi terhadap Kinerja Pegawai di Kantor Bupati Maros - Ramadani, Eka Fitra (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM), Sekolah Tinggi Ilmu Sosial dan Ilmu Politik (STISIPOL) Candradimuka, 2024)
This study aims to analyze the Effect of Organizational Culture on Employee Performance at the Maros Regent Office. This research was a quantitative research that shows a causal relationship. The sample in this study were 46 employees. Data collection techniques used were observation, interviews and questionnaires. Data analysis techniques used were descriptive statistical analysis using percentages, averages, and standard deviations using simple linear regression analysis techniques, coefficient of determination and hypothesis testing (t-test) with the help of SPSS 16.0 for Windows software. Simple regression analysis with the testing of research instruments using factor analysis to see the validity of the research instrument, reliability testing of research instruments, and testing for normality to see the distribution of data in the research variables.Based on the results of the research, it can be concluded that the organizational culture is in a very good category in terms of the t-control indicator, which is about supervision from the leadership of the employee, the respondent answers agree as much as 93%. Employee performance is in the fairly good category in terms of loyalty indicators, namely performance measured by employee loyalty to their duties and responsibilities in the organization, respondents answered agreeing as much as 91%. From the results of the study obtained the magnitude of the influence of organizational culture on employee performance by 38.5% and 61.5% influenced by other variables that have not been taken into account in this study.